Popularization of ideas on a healthy way of life on pages of printing editions of Bukovina (end ХІХ–beginning ХХ century) - Гнесь, Н. О. (Slobozhanskyi Herald of Science and Sport, 2011)
In article themes for popularization of ideas of a healthy way of life on pages of printing editions of Bukovina of end ХІХ are defined–beginnings ХХ. Are opened century ways of preservation of physical health: observance of personal hygiene, hygiene of premises, a diet that abilities to live, physical activity in the open air, temper. The maintenance of councils about rising generation education as pledge of moral improvement of the population of edge is defined.